ACL injury mechanisms: Lessons learned from video analysis - Koga , H.; Muneta, T.; Bahr, R.; Engebretsen, L.; Krosshaug, T. (Rotatory Knee Instability, 2016)
A detailed description of noncontact anterior cruciate ligament (ACL) injury mechanisms is crucial to develop ACL injury prevention programs. A model-based image-matching (MBIM) technique has enabled detailed video analysis of injury situations, a task previously limited to simple visual inspection. The current authors have analyzed 11 different ACL injury situations from videotapes using the MBIM technique. The knee kinematic patterns were remarkably consistent, displaying immediate valgus, internal rotation motion, and anterior tibial translation, all occurring within the first 40 ms after initial ground contact. Peak vertical ground reaction force occurred at 40 ms after the initial ground contact. Based on these results, it is likely that the ACL injury occurred approximately 40 ms after the initial ground contact. In contrast, hip joint angles remained unchanged at an internally rotated position during the first 40 ms after initial ground contact. Based on these results and previous key studies, we proposed a new hypothesis for ACL injury mechanisms: lateral knee compression caused by valgus loading and the anterior force vector caused by quadriceps contraction, causing a displacement of the femur relative to the tibia where the lateral femoral condyle shifts posteriorly, due to the joint geometry, and the tibia translates anteriorly and rotates internally, thereby resulting in ACL rupture. The fact that there is limited hip joint movement indicates that hip energy absorption may be limited, thus contributing to the injury. These results suggest that prevention programs should focus on acquiring a cutting and landing technique that avoids knee valgus and internal rotation during knee flexion and adequate hip flexion to absorb energy from ground reaction force, as well as avoiding excessive hip internal rotation. Moreover, the fact that the ACL injury occurs 40 ms after initial ground contact suggests that "feed-forward" strategies before landing, controlling knee and hip motion before landing, may be critical, as "feedback" strategies to correct inappropriate hip and knee motion after landing cannot prevent ACL injuries.